Brick-and-Platform: Listing Labor in the Digital Vintage Economy. (July 2020) - Kneese, Tamara; Palm, Michael
Vintage goods are valued for their nostalgic association with pre-digital modes of production, but their contemporary trafficking is increasingly organized by processes of platformization. The central component of what we call "listing labor in the digital vintage economy" is the online display of collectible merchandise, but listing labor also entails promoting sellers' brands on social media and using sales platforms and other logistical media to manage inventory, process transactions, and handle shipments. Listing labor is performed by branded merchants and their employees alongside independent entrepreneurs. The digital vintage economy connects brick-and-mortar shops and resale supply chains organized around flea markets, thrift shops and charity bins, estate sales, and consigners, to online clearinghouses like eBay and Craigslist, and to social media and payment apps. In this article, we argue that listing labor in the digital vintage economy further develops the concept of "platform labor." We focus on vintage clothes and vinyl records, dominated by women and men, respectively, to help us analyze divisions of listing labor organized by gender, race, age, and class. We draw upon 20 semi-structured interviews with shop owners and employees and on participant observation in independently owned clothing boutiques and record stores in several US cities. The digital vintage economy provides another angle for understanding how identity-based distinctions affect the opportunities associated with platform labor, and our account of listing labor highlights the need for studies of platformization that analyze its effects on specific local economies as well as on job markets and commercial sectors.